Correlation of CA125 with adnexsa tumors: A literature review - Sity Rahmatia Alimun; Syamsu Rijal; Ilham Arif (Holistik Jurnal Kesehatan, 2026)
Background: Adnexal tumors represent a broad spectrum of gynecological conditions ranging from benign lesions to malignant ovarian tumors with high mortality rates. Delayed diagnosis remains a major clinical challenge, particularly in ovarian cancer. Cancer Antigen 125 (CA125) is the most widely used biomarker for assessing the risk of malignancy in adnexal masses; however, its sensitivity and specificity are limited, especially in early-stage disease and non-malignant conditions. Previous studies have reported inconsistent results regarding the correlation between CA125 levels and adnexal tumors. Purpose: To analyze the correlation between CA125 levels and adnexal tumors. Method: A literature review with a meta-analysis approach was conducted following the PRISMA guidelines. Relevant studies published between 2015 and 2025 were identified through PubMed, Scopus, Web of Science, and ScienceDirect databases. Eligible studies were quantitatively analyzed to assess the strength of the correlation between CA125 levels and the nature of adnexal tumors. Statistical analyses were performed using fixed-effect or random-effect models based on inter-study heterogeneity. Results: The meta-analysis demonstrated an association between elevated CA125 levels and malignant adnexal tumors, although substantial variability among studies was observed. The heterogeneity reflected differences in study populations, menopausal status, diagnostic methods, and tumor histopathology. Conclusion: CA125 plays a supportive role as a biomarker in the evaluation of adnexal tumors, particularly for malignancy risk stratification and clinical monitoring. Nevertheless, due to its limited sensitivity and specificity, CA125 should not be used as a standalone diagnostic tool and must be integrated with clinical assessment and imaging modalities. This meta-analysis emphasizes the importance of a multimodal diagnostic approach in adnexal tumor management. Suggestion: Further research should involve a combination of other biomarkers and imaging examinations to improve the predictability of malignancy.   Keywords: Adnexal Tumor: Biomarker; CA125 Level; Ovarian Cancer.   Pendahuluan: Tumor adneksa merupakan masalah kesehatan ginekologi yang sering dijumpai dan mencakup spektrum luas dari lesi jinak hingga keganasan ovarium dengan mortalitas tinggi. Keterlambatan diagnosis, terutama pada kanker ovarium, menjadi tantangan utama dalam praktik klinis. Cancer Antigen 125 (CA125) merupakan biomarker yang paling banyak digunakan untuk membantu penilaian risiko keganasan tumor adneksa, namun memiliki keterbatasan sensitivitas dan spesifisitas, terutama pada stadium awal dan kondisi non-maligna. Bukti ilmiah mengenai korelasi CA125 dengan tumor adneksa masih menunjukkan hasil yang bervariasi. Tujuan: Untuk menganalisis korelasi antara kadar CA125 dengan tumor adneksa. Metode: Penelitian menggunakan pendekatan literature review dengan metode meta-analisis sesuai pedoman PRISMA. Penelusuran literatur dilakukan pada basis data PubMed, Scopus, Web of Science, dan ScienceDirect untuk artikel yang dipublikasikan pada periode 2015–2025. Artikel yang memenuhi kriteria inklusi dianalisis secara kuantitatif untuk menilai kekuatan korelasi antara kadar CA125 dan sifat tumor adneksa. Analisis statistik dilakukan menggunakan model fixed effect atau random effect berdasarkan tingkat heterogenitas antar studi.. Hasil: Adanya hubungan antara peningkatan kadar CA125 dengan sifat keganasan tumor adneksa, meskipun ditemukan variasi hasil antar penelitian. Heterogenitas antar studi mencerminkan perbedaan karakteristik populasi, status menopause, metode pemeriksaan, serta jenis histopatologi tumor. Simpulan: CA125 memiliki peran sebagai biomarker pendukung dalam evaluasi tumor adneksa, terutama dalam stratifikasi risiko keganasan dan pemantauan klinis. Namun, keterbatasan sensitivitas dan spesifisitas menegaskan bahwa CA125 tidak dapat digunakan sebagai alat diagnostik tunggal dan harus dikombinasikan dengan penilaian klinis serta modalitas diagnostik lainnya. Meta-analisis ini memperkuat pentingnya pendekatan multimodal dalam diagnosis tumor adneksa. Saran: Penelitian lanjutan sebaiknya melibatkan kombinasi penanda biomolekuler lain dan pemeriksaan pencitraan untuk meningkatkan prediktabilitas keganasan.   Kata Kunci: Biomarker; Kadar CA125; Kanker Ovarium; Tumor Adneksa.